2013
DOI: 10.1002/aenm.201200713
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating High Performance, Donor–Acceptor Copolymer Solar Cells by Spray‐Coating in Air

Abstract: We report the fabrication of high performance organic solar cells by spray‐coating the photoactive layer in air. The photovoltaic blends consist of a blend of carbazole and benzothiadiazole based donor–acceptor copolymers and the fullerene derivative PC70BM. Here, we formulate a number of photovoltaic inks using a range of solvent systems that we show can all be deposited by spray casting. We use a range of techniques to characterize the structure of such films, and show that spray‐cast films have comparable s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 35 publications
2
77
0
Order By: Relevance
“…The importance of the drying pathway has been recognised by several authors and has been found to considerably impact performances. [22][23][24]…”
Section: Annealing Protocolsmentioning
confidence: 99%
“…The importance of the drying pathway has been recognised by several authors and has been found to considerably impact performances. [22][23][24]…”
Section: Annealing Protocolsmentioning
confidence: 99%
“…Recently, the state-of-arts single junction OSCs with power conversion efficiency (PCE) approaching 9-10% have been achieved via interfacial engineering [5], device optimization [6] and rational material synthesis, e.g., p-type polymers PTB7 [7], PTB7-Th [8], PPDT2FBT [9] and PffBT4T-2OD [10]. However, the above mentioned OSCs are all fabricated based on conventional spin coating method, which is not capable of large-scale fabrication due to its significant waste of materials and limitation on the rigid substrates [11][12][13][14]. Until now, a variety of alternative deposition methods have been emerged including roll-to-roll [15], blade coating [16] and ink-jet printing [17] et al Although a large volume of researches using these techniques have been devoted in maintaining the PCE as high as those based on spin coating, the obvious declines of PCE could be observed for most of bulk heterojunction (BHJ) systems, e.g., P3HT:PC 61 BM and PTB7:PC 71 BM systems [18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, spray coating has been used in the fabrication of OPVs and is compatible with large area processing over flexible substrates. [11][12][13][14][15] Notably, most work on the development of spray cast…”
Section: Highlightsmentioning
confidence: 99%
“…[16] More recent work has however explored spray-cast blends of amorphous donor-acceptor co-polymers with fullerene-derivative electron acceptors, with improved device performance demonstrated. [11,13,17,18] Spray-coating has also been used to deposit the various charge transporting layers used in OPV devices. [19] In single junction OPV device based on a conventional architecture, the active layer is deposited onto a hole-transporting layer.…”
Section: Highlightsmentioning
confidence: 99%